Thymus algeriensis and Thymus fontanesii exert neuroprotective effect against chronic constriction injury-induced neuropathic pain in rats - Rezq, Samar (Sci Rep, 2020)
We have previously demonstrated that the Thymus algeriensis and Thymus fontanesii extracts have powerful anti-inflammatory, antipyretic, and analgesic effects against acute pain models. We profiled their chemical composition and found many phenolic acids, flavonoids, and phenolic diterpenes. In this work, we investigated their antioxidant properties on HaCaT cells exposed to UVA-induced oxidative stress and examined their effects against chronic neuropathic pain and the underlying mechanisms. Through a rat chronic constriction injury (CCI) model, we induced chronic neuropathic pain by placing 4 loose ligatures around the right sciatic nerve for 14 days. Thermal and mechanical hyperalgesia in addition to cold and dynamic allodynia were tested on the day before surgery and on the 7th and 14th post-surgery days. Key markers of the nitrosative and oxidative stresses, in addition to markers of inflammation, were measured at day 14 post surgery. Histopathological examination and immunostaining of both synaptophysin and caspase-3 of sciatic nerve and brain stem were also performed. Results of this study showed that T. algeriensis extract suppresses UVA oxidative stress in HaCaT cells via activation of the Nrf-2 pathway. Both extracts attenuated hyperalgesia and allodynia at 7- and 14-days post-surgery with more prominent effects at day 14 of surgery. Their protective effects against neuropathic pain were mediated by inhibiting NOX-1, iNOS, by increasing the enzyme activity of catalase, and inhibition of inflammatory mediators, NF-κB, TNF-α, lipoxygenase, COX-2 enzymes, and PGE2. Furthermore, they improved deleterious structural changes of the brainstem and sciatic nerve. They also attenuated the increased caspase-3 and synaptophysin. The data indicate that both extracts have neuroprotective effects against chronic constriction injury-induced neuropathic pain. The observed protective effects are partially mediated through attenuation of oxidative and nitrosative stress and suppression of both neuroinflammation and neuronal apoptosis, suggesting substantial activities of both extracts in amelioration of painful peripheral neuropathy.